PRELIMINARY RESULTS OF EXPERIMENTAL RESEARCH AND PSYCHOLOGICAL ANALYSIS OF MIMIC HUMAN REACTIONS USING SPECIALIZED SOFTWARE - Engalychev, V.F.; Leonova , V. E.; Khavylo , A.V.; Ghazaryan , G. H. (Modern Psychology, 2021)
Recently the technologies of diagnosing the mental state of a person according to his behavior recorded on video have become more and more in demand in the work of operational - investigative and forensic practice. Non-verbal activity of a person is determined by many factors: along with factors of external stimulus, culture and general specificity of non-verbal activity, psychological traits play an important role, including individual-typological personality particularities that must be taken into account in order to increase the reliability of conclusions in the analysis of observed behavior. There are various approaches to the interpretation of nonverbal behavior while a person is lying: 1) an emotional approach; 2) an approach based on the complexity of the content; 3) a behavioral control approach. To solve the problems of increasing the accuracy of psychological analysis of people's behavior in legally relevant situations, it is important to analyze not just the emotional reaction, but its correlation with the subjectively significant cognitive load of incentives (questions).
Keywords: non-verbal behavior, non-verbal activity, psychological particularities, cognitive load of incentives.